Uji Kompetensi Kelas Berbasis Penilaian Diri Pada Matakuliah Alat Ukur Listrik - Suari, Muharmen (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Research to measure the level of competency attainment of students tadris IPA Physics class A 2019 on the material of measurement, submaterial measurement’s defenition, measurement’s type and measurement’s important term in the electrical measuring instruments. This research has used a qualitative approach with descriptive research and case studies. Data collection techniques through self-application by students towards their level of competency using google serial forms. The results showed that the activeness of students in following learning is quite high. The level of readiness of students following the learning is quite good. In addition, based on the results of research can be seen that there is an improvement in material mastery competency after learning. This can be seen from the improvement of each component of competency before learning and after learning. In addition, the level of confidence in the correctness of the answers given in the pretest and posttest also increased. In addition, the research findings that students are still weak in learning competencies distinguish the level of precision and accuracy in measurement so that the material enrichment is required.